An enlightened aristocrat at the crossroads of countries and languages - Jaroslav Stanovský (Cornova)
This paper focuses on the personality of an important aristocrat from the Age of Enlightenment, Ignác Dominik Chorynský, as a person living and acting on the border of countries and languages, creating an extensive network of social and intellectual contacts around him. The vast personal archive of this nobleman conserved in Opava still awaits closer examination. Ignác Dominik Chorynský, a member of an old Moravian family, settled after 1750 in Velké Hoštice under Prussian domination, due to his marriage to Countess Barbora Hodic, while also being active in Opava, on Austrian territory. This paper examines the “frontier” position of Ignác Dominik from several aspects. The first is from the political aspect: the count was a subject of the King of Prussia and, at the same time, a regional governor in the Prussian and Austrian parts of Opava, still subordinate to the House of Habsburg. Moreover, his brother Jan Nepomuk fell in the Seven Years’ War against Prussia. Obviously, the position on the border also played a role in the representation of the count, as evidenced by the “Banquet Hall of Three Lands”, which he had built in Velké Hoštice. In the following portion, this paper presents Ignác Dominik’s wide network of contacts: amongst the local nobility in Silesia, amongst actors on the Prussian side (Frederick II, the nobles and intellectuals of Wrocław), and in Moravia (his brothers Matyáš and František Jan, Count Mittrowsky, etc.). This paper then delves into the theme of artistic transfers, as Ignác Dominik contributed to the cultural development of his region with his activities (building the castle in Velké Hoštice, rebuilding the so-called “Blücher Palace” in Opava, collecting works of art, etc.). Finally, this paper focuses on the possible role of Silesian and Prussian milieu on Ignác Dominik’s cultural activities. This paper also demonstrates the unique position of the Opava and Hlučín regions after the Wars of Austrian Succession and the imminent role of Ignác Dominik and his close friends in the cultural development of the region.